Acoustic enrichment can enhance fish community development on degraded coral reef habitat - Gordon, Timothy A. C. (Nat Commun, 2019)
Coral reefs worldwide are increasingly damaged by anthropogenic stressors, necessitating novel approaches for their management. Maintaining healthy fish communities counteracts reef degradation, but degraded reefs smell and sound less attractive to settlement-stage fishes than their healthy states. Here, using a six-week field experiment, we demonstrate that playback of healthy reef sound can increase fish settlement and retention to degraded habitat. We compare fish community development on acoustically enriched coral-rubble patch reefs with acoustically unmanipulated controls. Acoustic enrichment enhances fish community development across all major trophic guilds, with a doubling in overall abundance and 50% greater species richness. If combined with active habitat restoration and effective conservation measures, rebuilding fish communities in this manner might accelerate ecosystem recovery at multiple spatial and temporal scales. Acoustic enrichment shows promise as a novel tool for the active management of degraded coral reefs.